biomedicalresearch 2019
DOI: 10.35841/biomedicalresearch.30-18-1195
|View full text |Cite
|
Sign up to set email alerts
|

Identification of breed-specific SNP panel in nine different cattle genomes.

Abstract: Single nucleotide polymorphism (SNP) high-density chips are now serving as important bioinformatics tools for improvement and development of various livestock species. Major constraint being the high cost of protocol which is not feasible at the population level. Hence, in the present study, we have tried to reduce the SNP panel to a fewer number of informative markers which will be very much cost-effective. The 50K Illumina BeadChip genotypic data obtained from online Dryad repository for six indigenous cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Variants mapping on unplaced scaffolds were discarded. Breed-specific SNP files were obtained for the six subspecies from the vcf file containing the total SNPs with vcftools [ 29 ], and filtered according to Kumar et al [ 30 ]. Each breed-specific file was filtered with plink2 (--geno 0.05 --max-alleles 2 --maf 0.36) [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Variants mapping on unplaced scaffolds were discarded. Breed-specific SNP files were obtained for the six subspecies from the vcf file containing the total SNPs with vcftools [ 29 ], and filtered according to Kumar et al [ 30 ]. Each breed-specific file was filtered with plink2 (--geno 0.05 --max-alleles 2 --maf 0.36) [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that a small set of SNPs, if accurately chosen, is sufficient to differentiate the genetic origin of breeds [ 15 , 21 ]. In the case of the estimation of breed composition, Kumar et al [ 22 ] showed that a subset of 470 informative SNPs could discriminate six Indian indigenous and European dairy breeds. Using a combination of principal component analysis (PCA) and random forest, Hulsegge et al [ 23 ] identified 133 SNPs that allowed to differentiate local Dutch cattle breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Small sets, or panels, of ancestry informative markers (AIMs) have been developed and used to infer population genetic parameters in several species. AIM panels have been used to estimate biogeographical ancestry and structure in human populations [19][20][21][22], to discriminate among breeds and geographical origin of Italian sheep breeds [23], to identify cattle breeds [24][25][26], to trace the origin of animal products [27,28], and for breed assignment and analysis of individual ancestry in cattle [29][30][31][32] and pig populations [33]. Moreover, AIM panels have been developed to identify hybrids in wildlife conservation projects on wolf [34], wild cat [9], and mule deer [35].…”
Section: Introductionmentioning
confidence: 99%